Faricimab in the Treatment of Exudative Neovascular Age-Related Macular Degeneration and Diabetic Macular Edema in Italy: The FARIT Real World Study - Marco Lupidi; Cristiana Iaculli; Luisa Marco; Settimio Rossi; Emilia Sicari; Giulia Villa; Vittorio Pirani (Ophthalmology and Therapy)
Abstract Introduction Faricimab is a bispecific antibody that enables greater disease control and extended durability compared with vascular endothelial growth factor (VEGF) inhibition alone in neovascular age-related macular degeneration (nAMD) and diabetic macular edema (DME). This study aimed to evaluate its effectiveness, durability, and economic and social burden in Italian clinical practice. Methods FARIT was a retrospective, observational, multicenter cohort study across four Italian sites. Adult patients with nAMD or DME who initiated faricimab from February 2023 and had ≥ 6 months of follow-up were included. Clinical outcomes, treatment patterns, and patient-reported data were collected through chart review and electronic surveys. Results A total of 87 eyes (68 with nAMD, 19 with DME) were followed for a median of 14 months. Among them, 33 eyes (24 with nAMD, 9 with DME) were anti-VEGF naïve. At 1 year, 95.4% and 100% of naïve eyes with nAMD and DME, respectively, reached a dosing interval of every 12 weeks (Q12W) or longer; 63.6% and 100% received the treatment every 16 weeks (Q16W). Among switch eyes, 92.4% (nAMD) and 71.5% (DME) reached ≥ Q12W, with 35.9% and 42.9%, respectively, on Q16W dosing. After a full loading phase, the median number of injections administered during the post-loading follow-up period (12 months for nAMD, 10 months for DME) was three for nAMD and two for DME. The interval extensions were driven by visual acuity stabilization/improvement and fluid resolution. Patients and caregivers reported high satisfaction and reduced burden, with fewer injections and better visual outcomes contributing most to improved quality of life. Economic analysis showed a 12-month direct cost (excluding the drug cost) of 1223.8 €/patient from the healthcare system perspective. Conclusions Faricimab provided effective disease control and extended treatment intervals in treatment-naïve and previously treated eyes with nAMD and DME, showing a fast anatomical response and reduced injection burden.